The larva and life history of Stenophylax nycterobius (McLachlan, 1875) (Trichoptera: Limnephilidae) in high mountain streams (Sierra Nevada, Spain) and key to the Iberian larvae of the genus - Sáinz-Bariáin, Marta; Zamora-Muñoz, Carmen (Zootaxa, 2012)
The larva and pupa of Stenophylax nycterobius (McLachlan, 1875) were briefly, although insufficiently, described by Lepneva (1966). Here, the larva is fully described and figured. Its most important diagnostic features to distinguish it from other species are illustrated. A key is presented for the identification of the known Stenophylax larvae of the Iberian Peninsula. Descriptions of its habitat, life cycle and its particular life history in high mountain streams from the southeast of the Iberian Peninsula (Sierra Nevada) are included.